Avaliação de parâmetros químicos e mineralógicos de materiais cimentícios suplementares na mitigação da reação álcali agregado - Guillante, Patricia (Universidade do Vale do Rio dos Sinos, 2018)
Concrete structures produced with cements of high alkali content and reactive aggregates, when located in humid environments are prone to develop a chemical reaction known as the Alkali-Aggregate Reaction (AAR). In order to minimize the development of this reaction, the alkali content can be controlled by the use of non-reactive aggregates, although this does not guarantee the reaction complete mitigation. Another alternative is the use of mineral additions, especially pozzolans, whose benefit is associated with the fact that it consume calcium hydroxide to produce additional hydrated calcium silicate, reducing the permeability and mobility of alkalis inside concrete. Recent researches have shown that aluminosilicate pozzolanic materials present higher performance in AAR mitigation than siliceous materials. It is consensus that aluminum presence have a protagonist role. However, the mitigation behavior of AAR may be different depending on the type of pozzolanic material employed. Thus, the general objective of this work was to evaluate the influence of chemical and mineralogical parameters of aluminosilicate pozzolans in the mitigation of AAR. The accelerated mortar bars method was used to investigate the behavior of three mineral admixtures rich in silica and alumina: Fly Ash (FA), Metakaolin (MK) and Red Ceramic Waste (RCW). Two curing ages were considered - 48h and 28 days - and auxiliary mixtures with silica fume were used, with similar content of amorphous silica; with powder quartz to compose a secondary reference standard, allowing the evaluation of cement consumption reduction effect; and, to mark the evaluation of the aluminum content, mixtures with aluminum hydroxide [Al(OH)3]. The materials were characterized for physical, chemical and mineralogical parameters. The chemical composition of the pores aqueous solution of the mixtures and the microstructure of the reference mortar bars after the accelerated test were also analyzed. The aggregate was classified as an obsidian composed basically of volcanic glass and the results of the accelerated test indicate that the used pozzolans present mitigating potential, but at different levels. It was found that the curing time had no significant influence on the results, despite the slight increase of expansions measured in samples cured for 28 days, before the accelerated test. By incorporating Al(OH)3, a linear behavior of expansions was observed in which as higher the content of Al(OH)3, the lower the expansion values are. However, this behavior was not verified with the pozzolanic materials. The total aluminum content for MK, FA and RCW was 38%, 21% and 17%, respectively, resulting in expansions at the 28 day test of 0.03%, 0.02% and 0.08%. It is noteworthy that the lower expansion results were observed in the mixture with FA, which also presented aluminum concentration in the pore solution close to zero. It is known that alumina acts in the inhibition of the reactive silica dissolution by its incorporation in the silica structure, forming a kind of zeolite and, therefore, the characterization of the solution of the pores of the FA can also be an indicator of the greater effectiveness of the alumina from FA in the mitigation of AAR. In addition, it was observed that the mixture with RCW that the iron content, mainly identified in the hematite form, seems to interfere in the dissolution of the aluminum, which may have hampered the AAR mitigation potential by aluminum in this case. The crystalline or amorphous form of how these elements are present in pozzolans seem to influence the potential for mitigation. Thus, it is believed that not only the alumina content exerts influence on the expansion reduction, but also its mineral and crystalline structure, in which the aluminum present in the material may indicate its incorporation into the silica particles.
Keywords: Reação álcali-agregado; Mitigação; Materiais cimentícios suplementares; Aluminossilicatos; Alcali-aggregate reaction; Mitigation; Supplementary cementitious materials; ACCNPQ::Engenharias::Engenharia Civil